2019
DOI: 10.24036/jea.v1i2.104
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Regulasi, Politik Anggaran, Perencanaan Anggaran, Sumber Daya Manusia Dan Pengadaan Barang/ Jasa Terhadap Penyerapan Anggaran Belanja Pada OPD Provinsi Sumatera Barat

Abstract: This study aims to prove empirically the effect of regulation, budget politics, budget planning, human resources and the procurement of goods/services on budget absorption. This research is classified as causative research. The population in this study are 39 Regional Organizations (OPD) of West Sumatra Province. The sample in this study used the Total Sampling method. The type of data used in this study is primary and secondary data. Data collection techniques using a questionnaire consisting of 4 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 3 publications
1
10
0
7
Order By: Relevance
“…The proposed budget is more significant than required without considering the ease of implementation and real needs in the field. However, in contrast to (Ramdhani & Anisa, 2017;Putri et al, 2018;Ramadhani & Setiawan, 2019;Lannai & Amin, 2020) finding that budget planning has a positive and significant effect on budget absorption. Administrative records are vital so that they can be used as evidence of recording, decision making, and reporting to influence budget absorption properly.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The proposed budget is more significant than required without considering the ease of implementation and real needs in the field. However, in contrast to (Ramdhani & Anisa, 2017;Putri et al, 2018;Ramadhani & Setiawan, 2019;Lannai & Amin, 2020) finding that budget planning has a positive and significant effect on budget absorption. Administrative records are vital so that they can be used as evidence of recording, decision making, and reporting to influence budget absorption properly.…”
Section: Discussionmentioning
confidence: 83%
“…The results of this study support the stakeholder theory explaining that local governments have a reciprocal relationship between each party that will have an impact on one another in achieving specific goals, the government as a stakeholder whose influence is quite significant on development in the region provides services to the needs of the community by the process of procuring goods/services online which are one way to accelerate budget absorption. The study results (Gagola et al, 2017;Syakhrial, 2018;Ramadhani & Setiawan, 2019) found that the procurement of goods/services had a positive and significant effect on budget absorption. However, Puluala (2021) found that the procurement of goods/services had a positive and insignificant impact on budget absorption.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations